THE DEVELOPMENT OF PHONEME PARADIGMS OF LINGUISTIC SIGN GRADATION IN VARIOUS LANGUAGE SYSTEMS - Azimova, Dilobarxon (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
Phoneme paradigms of linguistic sign gradation—systematic alternations of phonemes within lexemes signaling morphological, semantic, or prosodic contrasts—appear across diverse, often unrelated language families. This article examines how such paradigms develop, compares major types of gradation (vowel ablaut, consonant gradation, templatic alternation, reduplication, and tonal/ prosodic alternation), and synthesizes mechanisms that underlie their emergence and maintenance: phonetic/phonological conditioning, morphologization and grammaticalization, analogical leveling, prosodic reanalysis, and contact-induced diffusion. Representative case studies from Indo-European, Finnic, Semitic, Austronesian, and Bantu languages illustrate convergent developmental paths and typological variation. The article concludes with methodological recommendations for future research and discusses theoretical and applied implications for typology, acquisition, and computational modeling.